Pemodelan Sebaran Polutan Udara dari Flarestack Menggunakan AERMOD di Onshore Receiving Facilities PT X - Mochammad Yordan Royan Futari; Munawar Ali (Jurnal Serambi Engineering, 2025)
This study aims to model the dispersion of air emissions (NOₓ and SO₂) from the flarestack at the Onshore Receiving Facilities (ORF) of PT X using AERMOD software. Wind patterns affecting the emission distribution were analysed using WRPLOT View software. The modelling results were verified with ambient air quality measurements to ensure accuracy and reliability. The windrose analysis showed that wind directions shifted between semesters: west-to-east in semester I and east-to-west in semester II of 2023, affecting the dispersion patterns. Isopleth maps showed that NOₓ and SO₂ concentrations remained stable, with maximum concentrations of 0.28 µg/m³ and 0.028 µg/m³, respectively. Concentrations of both pollutants complied with Indonesia's air quality standards (Government Regulation No. 22/2021). However, actual ambient measurements showed higher concentrations due to external sources not included in the model. These results highlight the important role of meteorological factors in emission dispersion and the need for comprehensive pollution control strategies.